Methods and Techniques for Design of Effective and Competitive Single Wagon Load Transportation - Michal Kohani; Peter Marton (Communications - Scientific letters of the University of Zilina, 2009)
European freight railway operators are losing money with their single wagon load transportation activities. Closing down this business segment does not appear to be a valid option, since single wagon load transportation is connected with full train load business and intermodal traffic. This paper presents methods and techniques that were chosen to solve different problems of single wagon load transportation.